The association of folate and depression: A meta-analysis. (December 2017) - Bender, Ansley; Hagan, Kelsey E.; Kingston, Neal
Abstract: Background: Previous research suggested that folate levels play an important role in the etiology and course of depression. However, the literature has been inconsistent with regard to differences in folate level between individuals with and without depression. The present meta-analysis synthesized the results of previous studies to examine whether individuals with depression had lower levels of folate than individuals without depression. Methods: Meta-analytic procedures were conducted in accordance with PRISMA guidelines. Studies evaluating folate levels in individuals with and without depression via red blood cell folate, serum folate, or dietary intake of folate methods were identified via PsycINFO and PubMed. Random-effects meta-analysis was conducted using Hedge's g, and moderation analysis was used for both folate measurement method and population type. Study heterogeneity was assessed with I 2 and publication bias was qualitatively assessed via funnel plot and quantitatively assessed with the trim-and-fill method and Begg's adjusted rank test. Results: We found a significant, small effect size, such that individuals with depression had lower folate levels than those without depression, Hedge's g  = −0.24 (95% CI = −0.31,  −0.16), p  < 0.001. Study heterogeneity was high ( I 2  = 84.88%), and neither folate measurement method nor population accounted for study heterogeneity. Conclusions: Individuals with depression have lower serum levels of folate and dietary folate intake than individuals without depression. Given that previous literature suggested folate supplementation improved the efficacy of traditional antidepressant medications, future research on folate supplementation in depression is warranted and clinicians may wish to consider folate supplementation for patients with depression. Highlights: The study evaluated levels of folate in persons with and without depression. There was a small effect of depression on folate levels, such that persons with depression had lower levels of the nutrient. Supplementation with L-methylfolate may be advantageous for persons with depression.